Rare Intra-Aortic Migration of Temporary Epicardial Pacing Wire - Sharma, Arun; Arya, Shivali; Mahajan, Sachin; Bansal, Vidur; Singhal, Manphool (Indian Journal of Radiology and Imaging, 2023)
Temporary epicardial pacing wires are used routinely in the postoperative period to prevent brady-arrythmias and maintain hemodynamic condition. Their safety and efficacy have been widely accepted with a low incidence of complications. Complications associated with temporary epicardial pacing wires may occur during removal or may be related to retained wires. Migration is one of the well-established but rare complications of retained epicardial pacing wire. Though migrations to various organs have been well documented in the literature, there are only few reports on intra-aortic migration of pacing wires in the postoperative period. Further, it is important for radiologists to know and identify these epicardial pacing wires as they may be associated with complications like superadded infection, migration to surrounding or distant areas, and injury to the heart and vessels.
Keywords: temporary epicardial pacing wires; intra-aortic migration; pacing wire; CT angiography